Hybrid Precoder and Combiner Design for Single-User mmWave MIMO Systems - Zhang, Ran; Zou, Weixia; Wang, Ye; Cui, Mingyang (IEEE access, 2019)
wave (mmWave) communications have been regarded as a key technology for the next generation cellular systems since the huge available bandwidth can potentially provide the rates of multiple gigabits per second. In mmWave multiple-input multiple-output (MIMO) systems, the conventional precoding is infeasible due to the hardware cost and power consumption. Therefore, hybrid precoding is considered as a promising technology to provide a compromise between hardware complexity and system performance. In this paper, we investigate the designs of the hybrid precoder and combiner in mmWave MIMO systems. We adopt the hierarchical strategy to design a hybrid precoder to maximize the spectral efficiency. In particular, we focus on the optimization of analog precoder and propose a novel iterative algorithm. Then, based on the optimal analog precoder, we compute the digital precoder to improve the spectral efficiency. For practical implementation, the proposed hybrid precoder design can be used in wideband systems with orthogonal frequency division multiplexing modulation. The simulation results and mathematical analysis show that the proposed algorithm can achieve near-optimal performance with low complexity for mmWave MIMO systems.